Validation of Relapse Risk Biomarkers for Routine Use in Patients With Juvenile Idiopathic Arthritis - Rothmund, Friederike; Gerss, Joachim; Ruperto, Nicolino; Daebritz, Jan; Wittkowski, Helmut; Frosch, Michael; Wulffraat, Nico M.; Wedderburn, Lucy R.; Holzinger, Dirk; Gohar, Faekah; Vastert, Sebastiaan J.; Brik, Riva; et al. (Wiley-Blackwell, 2014)
Objective. The myeloid-related proteins 8 and 14 (MRP-8/MRP-14) and neutrophil-derived S100A12 are biomarkers of inflammation. They can be used to determine the relapse risk in patients with juvenile idiopathic arthritis (JIA) after stopping antiinflammatory treatment. In this study, we tested the performance of different enzyme-linked immunosorbent assays (ELISAs) in order to validate systems available for routine use.Methods. MRP-8/MRP-14 and S100A12 serum concentrations of 188 JIA patients in remission were analyzed. Commercially available test systems were compared to experimental ELISAs established in house. The ability of the assays to identify JIA patients at risk for relapse was analyzed.Results. For MRP-8/MRP-14, the PhiCal Calprotectin and Buhlmann MRP8/14 Calprotectin ELISAs revealed hazard ratios of 2.3 and 2.1, respectively. For S100A12, the CircuLex S100A12/EN-RAGE ELISA revealed a hazard ratio of 3.1. The commercial assays allowed a JIA relapse prediction that was at least comparable to the experimental ELISAs.Conclusion. For the prediction of JIA relapse after stopping medication, the biomarkers MRP-8/MRP-14 and S100A12 can be determined by using assays that are available for routine use. The tested commercial MRP-8/MRP-14 and S100A12 ELISAs showed a performance comparable to well-established experimental ELISA protocols when assay-specific cutoffs for the indication of relapse prediction are thoroughly applied.